The impact of outcome-based education on the mental health of university students - Wang Meng; Xie Neng-gang; Liu Dan-dan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This research study measures the analysis related to education on the mental health of university students. This research was conducted in China and describes the major business in today's University students. The research study based on primary data analysis for gathering the data used specific questions related to the variables included major business, university sports activities included a commitment of sports activities, the time spent on Sport, etc. These are all considered variables for gathering the data used 100 plus respondent participants related to the university students sports and businessman of sports industries. Measuring the data used different techniques and run informative results; for this purpose, smart PLS software was used to run informative results. Descriptive statistical analysis, the correlation coefficient, regression, model fitness analysis also describe that reliability, validity, and graphical analysis related to the major business in today's and sports activities of university students performance. The overall result shows a significant relationship between the significant business and university students sports related to the commitment of sports activities.